Interpretive reasoning - Stern, Laurent (Cornell University Press, 2005)
"Laurent Stern here provides a concise account of the difficulties that arise within the interpretive process and in the context of interpretive conflict. Speakers and agents are expected by others to be occasionally insincere. Attempting to be tolerant of alternative interpretations, and dealing with the insincerity of others, often motivates interpreters themselves to become insincere. Accordingly, moral issues emerge for both speakers and interpreters. Interpretive Reasoning discusses such issues in the literature on interpretation."